The Change of Mental Process in the Translation of Ronggeng Dhukuh Paruk from Bahasa Indonesia into English - Khristianto, Khristianto (State Institute of Islamic Studies Salatiga, 2015)
Mental process (thinking activities) is a part of transitivity system, representing language meaning as a symbol or representation meaning. In translation, this meaning is the most important, determining whether or not a clause is translated correctly. It means a sentence with a mental-process predicate will be right only, if it is realized in the same process. This paper tries to prove this notion, by exploring a novel translation from Bahasa to English. It employs Hallidayâs transitivity as a means to contrast a source text (T1) and a target text (T2).Based on the analysis, it is found out that some mental processes in the novel are translated into another process. Perception and affection are two subtypes of mental process which are translated into relational process and material process. The change into relational process is identified in many cases; though most of the data are translated into a the same mental process. This change is triggered by the strategies of modulation and transposition. Meanwhile, there is only a single case of change into a material process, which is resulted from the different realization, literal to metaphorical expression. Thus, this proves that the change of a process in a clause does not necessarily entail a change of meaning.Â